Effect of Discharge Readiness on 30-Day Readmissions Among Older Adults Living With Multiple Chronic Conditions - Pogue, Colleen A; Schlak, Amelia E; McHugh, Matthew D (Medical care, 2024)
Despite decreases in readmissions among Medicare beneficiaries after the implementation of the Hospital Readmissions Reduction Program, older adults living with multiple chronic conditions (MCCs) continue to experience higher readmission rates. Few strategies leverage nursing to identify patients at risk for readmission. Examine the effect of nurse assessments of discharge readiness on 30-day readmissions. Cross-sectional study linking 3 secondary data sources (ie, nurse survey, hospital survey, and Medicare claims data) representing 424 hospitals. A total of 188,806 Medicare surgical patients with MCCs. Discharge readiness was derived from the 2016 RN4CAST-US survey. Medicare claims data was used to determine the MCC count. The outcome was 30-day readmissions across the MCC count. The average discharge readiness score was 0.45 (range=0-0.86) indicating that, in the average hospital, <50% of nurses were confident their patient or caregiver could manage their care after discharge. Nearly 8% of patients were readmitted within 30 days of discharge; the highest rates of readmissions were among individuals with ≥5 MCCs (4293, 13.50%). For each 10% increase in the proportion of nurses in a hospital who were confident in their patients' discharge readiness, the odds of 30-day readmission decreased by 2% (95% CI: 0.96-1.00; P =0.028) for patients with 2-4 MCCs and 3% (95% CI: 0.94-0.99; P =0.015) for patients with ≥5 MCCs, relative to patients with 0-1 MCCs. Nurse assessments of discharge readiness may be a useful signal for hospitals to reduce readmissions and examine factors interfering with discharge processes.